Lean healthcare aplicado a central de material e esterilização: revisão integrativa de literatura - LOURENÇO, Marlon Lobato (2020)
In order to improve the care provided by the Nursing team, the adoption of new forms of health service organization that promote comprehensive and quality care in services has been discussed. To analyze the scientific production on the application of Lean Healthcare in Material and Sterilization Center (CME). From an integrative literature review, the LILACS, MEDLINE and CINAHL databases were selected for their comprehensiveness, great variability of content and full text available, the search was performed separately, in both searches the descriptors were combined. . In total 29 codes were created divided into 5 categories, the coding was thus grouped by the theoretical approximation respectively, starting with the analysis method, state of health organizations, which waste found in organizations, which Lean tools were used and which results obtained with the method; thus creating a chronological order that allowed us to glimpse the differences and similarities of the method in different hospitals. The implementation of the Lean method had a high adaptation in the hospitals where it was used, even though from different needs organizations modifications were necessary to reinvigorate the flow of people, materials and information. Health teams, especially those at the CME and Surgical Center, have benefited greatly from the fact that Lean provides a change in work habits, with an improved flow professionals reporting reduced occupational stress, improved communication and interpersonal relationships and Intersectoral, as well as a reduction in the costs to accomplish the tasks.